DAMPAK NEGATIF HUBUNGAN INCEST YANG TERGAMBAR DALAM DRAMA OEDIPUS, THE KING, KARYA SOPHOCLES - Syam, Essy (Jurnal Ilmu Budaya, 2008)
Incest, sexual intercourse done by people with blood relation, is forbidden with incest taboo, in most societies.